The role of support group and duration of infection in HIV/AIDS patients' knowledge and attitudes to their illness (2007)
To assess the association between support group membership, socio-demographic and HIV related factors including knowledge and attitude of illness in people living with HIV/AIDS (PLWHAs). Seventy six participants with HIV who were on follow-up management at three non-governmental care and treatment agencies in south western, Nigeria were asked to complete a questionnaire detailing their demographic characteristics, duration of awareness of HIV status, medication status, membership of a support group, HIV-related knowledge (including number of workshops/seminars attended, reading of literature), and attitude toward their illness and treatment. Compared to those who did not belong to a support group, (34,45%), those who did (42, 55%) were significantly more knowledgeable about HIV related (t= 4.02, p=0.00) and also reported more favorable attitudes toward the illness and its treatment (t=3.38, p=0.005). A multiple regression analysis indicated that group membership and a longer period of awareness of HIV infection contributed significantly to illness knowledge and attitudes. Age, sex, years of education, medication status, and employment status did not contribute significantly to these outcome variables. Individuals living with HIVI AIDS who belonged to a support group and had availed themselves of relevant literature were more knowledgeable and positive about their illness than those who did not belong to support groups. HIVI AIDS support group membership is an important component of psycho-social care in HIVIAIDS patients in Nigeria and should be encouraged.